(untitled) (Web of Teachers: Inderscience Research, 2026)
This article analyzes the role of integrated education, modern online learning platforms, and digital assessment systems in the training of specialists in radiation diagnostics and therapy. The study highlights the advantages of integrating radiology, radiation therapy, and radiation safety disciplines, the effectiveness of distance learning technologies, and modern approaches to digital assessment and monitoring of student performance. The importance of e-learning platforms and digital evaluation systems in developing professional competencies is also emphasized.